2020
DOI: 10.30998/sap.v4i3.6283
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas E-Learning Terhadap Hasil Belajar Mahasiswa Pada Mata Kuliah Konsep Dasar IPS

Abstract: Pemanfaatan <em>e-learning</em> pada pembelajaran di Prodi PGSD STKIP Modern Ngawi dilaksanakan untuk meningkatkan pembelajaran mahasiswa dalam pemahaman materi perkuliahan. Tujuan dari penelitian ini adalah mengungkapkan keefektifan media <em>e-learning</em> dalam meningkatkan pemahaman mahasiswa pada mata kuliah konsep dasar IPS yang ditunjukkan melalui hasil belajar mahasiswa. Penelitian dilaksanakan pada tahun 2020 dengan melibatkan 50 mahasiswa PGSD STKIP Modern Ngawi. Teknik pengu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
5
0
4
Order By: Relevance
“…This is indicated by the problem-solving ability of students meeting the minimum completeness criteria and student responses to learning in the positive category. Khusniyah (2020) found that learning using e-learning media has proven to be effective in increasing student understanding in social studies basic concepts, especially the social studies position material in the 2013 curriculum. It is proven by an increase in the average achievement of students' cognitive learning outcomes after learning.…”
Section: Figure 5 Student Learning Outcomes In Online Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…This is indicated by the problem-solving ability of students meeting the minimum completeness criteria and student responses to learning in the positive category. Khusniyah (2020) found that learning using e-learning media has proven to be effective in increasing student understanding in social studies basic concepts, especially the social studies position material in the 2013 curriculum. It is proven by an increase in the average achievement of students' cognitive learning outcomes after learning.…”
Section: Figure 5 Student Learning Outcomes In Online Learningmentioning
confidence: 99%
“…The facts related to the use of various other types of online platforms at various universities in Indonesia show mixed results. The implementation of learning using elearning can significantly improve student learning outcomes (Diantari et al, 2018;Khusniyah, 2020;Kurtz, Tsimerman, & Steiner, 2014). The implementation of learning through e-learning was quite effective for students (Ardini, Iswara, & Retnani, 2020;Irawan, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Evaluasi ini merupakan catatan pencapaian hasil dan keputusankeputusan untuk perbaikan dan aktualisasi pembelajaran. Evaluasi hasil belajar merupakan proses untuk menentukan nilai belajar peserta didik melalui kegiatan penilaian dan/atau pengukuran hasil belajar [9]. Dalam penelitian ini indikator yang diteliti adalah hasil penilaian terhadap peserta meliputi nilai pretest, posttest, ujian komprehensif, dan ujian ulangan (remedial) yang dikaitkan dengan karakteristik peserta diklat.…”
Section: Pendahuluanunclassified
“…Selanjutnya aktivitas peserta didik menunjukkan partisipasi dan keaktifan peserta didik selama proses pembelajaran berlangsung dengan baik dan respon peserta didik terhadap Model pembelajaran berbasis E-Learning berbantuan LKPD elektronik bersifat baik. Hasil penelitian ini sejalan dengan hasil penelitian (Khusniyah, 2020) yang menyebutkan bahwa pembelajaran berbasis e-learning efektif dalam meningkatkan hasil belajar.…”
Section: Pembahasanunclassified